Moda, artesanato e imaginário social: o Slow fashion como potência simbólica na sociedade pós-moderna - Vieira, Suellen Cristina (2020)
This research aims to enlighten the understanding of the culture of feelings and sustainability in fashion, such as which new paths towards conscious consumption and productive processes emerge. Thus the Slow Fashion movement and the valorization of handicrafts, as the central themes of this study, support the debate on the possibility of a new moment in the fashion system, through the management of regeneration and refraction of wear and tear caused by massification and the a consumer society. Based on the Theory of the Imaginary, referenced by Gilbert Durand and Michel Maffesoli, this research aims to understand how cultural load, using crafts, adds symbolic value to fashion products and studies the process of decelerating the industrial productive method? In this context, based on such questioning, a case study was carried out about the Leafy Natural Couture brand, adopting a Comprehensive Sociology as a methodological substrate, associated with a Symbolic Hermeneutics, seeking to identify itself as potent symbolic rules govern or Slow Fashion movement in postmodern society and understand how it is done or stimulate the exchange of knowledge between fashion professionals and artisans in order to design and develop products with “aura”. In this edition, an investigation gains materials contained from the analysis of a short film shown by the brand on its YouTube channel, in correlation with narratives of a group of nine women who develop craft work with a crochet technique for the brand. Thus it was possible to understand the main aspects that can be done in the process of decelerating the industrial production method and identify some relevant points, such as: Aesthetic and Symbolic Aura, Space-time, New Economy, Affection and Emancipated Creation. Therefore the repercussion of the results presented or the awakening of consciousness and a new discourse that demands, clarifies and places as new fashion brands an end that can create and develop a product that replaces identity and affection.